Analysis of mortality decline along with age and latent congenital defects - Dolejs, Josef (Mechanisms of ageing and development, 2003)
Mortality from congenital anomalies is inversely proportional to age after the age of 1 year. The theory of congenital individual risk explains this mortality decline. The overall aim of this study is to test whether the theory describes mortality decline for all diseases within the first year of life and after the age of 1. Mortality decline along with age was analyzed in five countries and for all causes of death. The theory of congenital individual risk describes well the real mortality decline for all diseases except malignant neoplasms after the birth. Decline of mortality is due to the dying out of the more impaired individuals. Mortality decline with the first power of age results from the selection before the birth. It is dominant and the frequency of defects decreases proportionally to the value of individual risk of death. In the case of identically probable defects, the selection does not occur and mortality declines with the square of age. Congenital defects were also identified as a cause of death in the case of infectious diseases occurring before the age of 10. Mortality from malignant neoplasms is age-independent within the age period 1-20 years and, contrary to all other diseases, no small subpopulation with a significant individual risk was identified.
Keywords: vrozené vady; rizikové faktory; Aging; nádory; analýza přežití; Communicable Diseases; Neoplasms; Risk Factors; lidé; Survival Analysis; statistické modely; Models, Statistical; Nonlinear Dynamics; Congenital Abnormalities; infekční nemoci; nelineární dynamika; stárnutí; Humans